Constructions of logical expressions in analysis of vegetation transformations - Łaska, Grażyna (Ecological Questions, 2008)
The paper reports on the effects and range of anthropogenic pressure exerted on forest communities of the Knyszyńska Forest. A comparison between the potential natural vegetation and real vegetation gives an idea on the degree of damage to forest communities, which has been classified in ecological modelling. Logical expressions have been applied in ecological modelling for spatial analyses of vegetation changes carried out by the program ArcView GIS. The logical expressions applied to the GIS spatial database have permitted finding correlations of occurrence of particular types of the present-day real vegetation (in particular the post-clear-cutting communities, young tree communities and secondary forest communities) relative to the present-day potential natural vegetation. The data obtained in this way have been used in analysis of the scale and range of changes in the forest communities of the Knyszyńska Forest caused by forest management measures. Results of the study have shown that in the Knyszyńska Forest, the secondary communities occupy as much as 88.3% (919.56 km2), while the oldest tree-stands representing natural communities (of 100 - 120 years of age) occupy only 11.7% (122.28 km2). Among the secondary communities the greatest area is occupied by the secondary forest communities representing the stickstand and oldgrowth phases (66.9%) aged from 30 to about 100 years. The contribution of young tree stands - aged from 10 to 30 years is smaller - 16.6%, and that of post-clear-cutting and forest crops forming directly after clear cutting and aged up to 10 years is still smaller - of 4.8%. In the young-tree stands (16.6%) and forest secondary communities (66.9%) the largest is the contribution of those with domination of pine trees (Pinus sylvestris) from artificial reforestation, making 11.2 and 55%, respectively, while the contribution of other secondary communities is much lower.